An unsupervised person re‐identification approach based on cross‐view distribution alignment. Issue 11 (13th May 2021) - Jia, Xibin; Wang, Xing; Mi, Qing
Abstract: Unsupervised clustering is a kind of popular solution for unsupervised person re‐identification (re‐ID). However, due to the influence of cross‐view differences, the results of clustering labels are not accurate. To solve this problem, an unsupervised re ID method based on cross‐view distributed alignment (CV‐DA) to reduce the influence of unsupervised cross‐view is proposed. Specifically, based on a popular unsupervised clustering method, density clustering DBSCAN is used to obtain pseudo labels. By calculating the similarity scores of images in the target domain and the source domain, the similarity distribution of different camera views is obtained and is aligned with the distribution with the consistency constraint of pseudo labels. The cross‐view distribution alignment constraint is used to guide the clustering process to obtain a more reliable pseudo label. The comprehensive comparative experiments are done in two public datasets, i.e. Market‐1501 and DukeMTMC‐reID. The comparative results show that the proposed method outperforms several state‐of‐the‐art approaches with mAP reaching 52.6% and rank1 71.1%. In order to prove the effectiveness of the proposed CV‐DA, the proposed constraint is added into two advanced re‐ID methods. The experimental results demonstrate that the mAP and rank increase by ∽ 0.5–2% after using the cross‐view distribution alignment constraint comparing with that of the associated original methods without using CV‐DA.